Kitâb el-İkdü’l-Ferîd - 880-01 İbn Abdürabbih, 860-940. (Kahire Kahire Kahire Kahire Kahire Kahire Kahire)
7 cilt (1. c. [11], 411 sayfa ; 2. c. 583 sayfa ; 3. c. 507 sayfa ; 4. c. 532 sayfa ; 5. c. 522 sayfa ; 6. c. 478 sayfa ; 7. c. [1], 296 sayfa)